“Let’s Talk”: Promoting Dialogue and Answerability in Critical Humanities Education with Permeable Curriculum and an Adda-Based Pedagogy - Dutta, Ritam (Kultura-Społeczeństwo-Edukacja, 2015)
Building on Moje et al and Dyson’s work within a Bakhtinian framework of dialogism and ethics of answerability, the paper argues the need for a critical humanities educator to create dialogic learning spaces within classrooms that would be engaging for students and where students would be encouraged to draw from their various ‘funds of knowledge’ in order to connect their ‘school-world’ with their other social worlds. The paper points out the interconnected nature of our knowing-in-the-world and suggests that all teachers, but especially teachers of critical humanities or social sciences adopt an adda-based pedagogy through a permeable curriculum for promoting wholesome, student-cantered learning in colleges and universities that would harness students’ various ‘funds of knowledge’ both in and outside classrooms. The paper argues that even though the use of adda in the classroom, like other similarly negotiated curricula, does generate some challenges for educators, yet the benefits of using an adda-based pedagogy in the classroom far out-weigh its disadvantages in the creation of a democratic, equitable and engaging learning environment in classrooms.